ATTENTIONAL STRATEGY AND TENNIS PERFORMANCE (Fiep Bulletin - online, 2015)
In sport, the adjusted attentional focus use can assits to better performance. In tennis, this can be highly relevant, mainly in the serve, which is nowadays on of the most important tennis strokes. The study objective was to verify the tennis serve performance differences between tennis players using external and internal attentional fcous. 12 tennis players were selected and divided in two groups. The subjects served trying to hit targets. The first group was performing with na external focus and the other one with na internal focus. Results were analysed, calculating the mean, standard deviation (SD)and variance. The exrternal focus group achieved a 26,33 points and the internal group reached 22 points, with a SD of 7,03 for the fisrt group and 5,71 for the second. The results are in the same way of those reveled by previous researches realized with other sports, confirming a possible relation between external attentional focus and tennis serve performance.
Keywords: Tennis; attention; sport psychology.